Pengaruh Lingkungan Keluarga terhadap Kepatuhan Tata Tertib Siswa Kelas Tinggi SD - Abd Hafid; Satriani, DH Satriani, DH; Weni Safitri (Universtas Negeri Makassar, 2022)
This research is a quantitative research with an ex post facto correlational model that aims to determine the effect of the family environment on the discipline compliance of high grade students of SD Inpres 12/79 Jeppe'e. The population in the study was high-class students with 134 students, while the sample was 50% of the total student population, namely 67 people. The data analysis technique is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, the students' family environment is in the good category with an average of 90,89 and a percentage of 75,74%. Student discipline compliance is in the good category with an average of 91,26 and a percentage of 76,05%. The results of inferential statistical analysis show that the t-count value (3.9069) is greater (>) than the t-table value (1.66864) at a significance level of 5%. Thus H0 is rejected and H1 is accepted. It can be concluded that there is a significant influence between the family environment on student discipline compliance at SD Inpres 12/79 Jeppe'e, Tanete Riattang Barat District, Bone Regency.